The Effect of Product Quality, Price, and Brand Image on Purchasing Decisions for Bango Soy Sauce Products in Cirebon City, West Java - Hafizh Ihsanudin; Muhammad Azhar Alifiandra; Mutia Intan Savitri Herista (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study aims to analyze the effect of product quality, price, and brand image on consumer purchasing decisions for Bango Soy Sauce in Cirebon City. The method used in this research is descriptive quantitative with the cluster area method, namely the Supermarket area and the Market area, stalls, etc., where data is collected through questionnaires distributed to 100 respondents who have used Kecap Bango products for at least three months. The results showed that product quality, price, and brand image significantly influenced purchasing decisions. Product quality has a significant positive effect, indicating that high-quality products can increase consumer buying decisions. Price also has a positive impact, although not as strong as product quality, which suggests that competitive prices can attract consumers. Brand image contributes to consumer loyalty, where a strong brand image can increase purchasing decisions. In addition, the simultaneous test results show that the three variables have a positive and significant influence on purchasing decisions.